Histological Evaluation of Direct Pulp Capping with Silk Sericin: A Preliminary Animal Study - Hartmann, Giovani Ceron; Brancalhão, Rose Meire Costa; Ribeiro, Lucinéia de Fátima Chasko; Rangel, Ana Lucia Carrinho Ayroza; Brandão, Christian Giampietro (Iranian Endodontic Journal, 2019)
Introduction: This histological study analyzed silk sericin as a potential direct pulp capping biomaterial in contact with pulp and comparing its response to calcium hydroxide. Methods and Materials: Twenty maxillary first molars from Wistar male rats were used, with 60 days of age, between 200 and 300 gr, which were divided in 4 groups (n=5): G1 and G3, controls, capped with calcium hydroxide in 7 and 30 days, respectively; G2 and G4, capped with silk sericin in 7 and 30 days, respectively. Circular cavities were prepared for pulp exposure, where capping materials were applied, being posteriorly restored with glass ionomer cement. After completion of each observation period, the animals were sacrificed and molars were histologically processed for analysis in light microscopy to evaluate presence of necrosis in pulp tissue, inflammatory cells infiltration and tertiary dentin formation. Data analysis was carried out using Kruskal-Wallis and Dunn’s post hoc tests. Results: After 7 days, there was less necrosis and inflammatory cells infiltration in G1 when compared to G2 (P=0.007 and P=0.008, respectively). After 30 days, a sample of G3 induced tertiary dentin formation and G4 showed decrease in inflammation (P=0.041) compared to G2. Conclusion: Among the determined experiment conditions, it was concluded that contact between silk sericin and pulp tissue showed improved inflammatory response throughout treatment and new cells proliferation. However, silk sericin adhibition in pure form did not show capability for induction of tertiary dentin formation. Keywords: Biocompatible Materials; Calcium Hydroxide; Dental Pulp Capping; Sericin <!–[if !supportAnnotations]–> <!–[endif]–>